Mosque study programme (MSP) project in Gombak: A model of university-community engagement (UCE) project at the International Islamic University Malaysia (IIUM) - Abdul Jalil, Mohd. Noh (2019)
The role of mosque as a uniting and harmonizing agent particularly for all Muslim individuals in a community, and between Muslim and Non-Muslim members of the society has been historically proven. In the present Malaysian context, these significant roles of the mosque could be revived with the development of a much more structured religious curriculum for mosque, which serve the spiritual and intellectual needs of various different groups in the society. Basically this project comprises of two phases. First it will conduct a survey on existing teaching modules that are used by mosque teachers in Gombak, and then identify areas of concern. Based on this information the project will then work on building a standard and comprehensive curriculum that will serve as a better alternative to the existing ones.